CHALLENGES IN THE TREATMENT OF ORBITAL FRACTURES: A SURGICAL APPROACH - Lopez, Andres Santiago Quizhpi; Albino, Raiany Stephanie; Galvao, Victoria Regina Schickinoe; de Oliveira, Luiz Eduardo Prestes; Marques, Vinicius Sai; da Silva, Vanessa Peixoto; Poletto, Gustavo; da Costa, Elizângela Bonetto; Machado, Camila Eduarda Koehler; Gomes, Wisley Rafael Fulber; da Silva, Leandro Stefanini; de Almeida, Ana Clara Ribeiro Freire (Seven Editora, 2026)
Orbital fractures represent a significant challenge in facial traumatology, accounting for approximately 3% of emergency room visits (Zhou et al., 2021). The anatomical complexity of the orbit, composed of multiple bones and delicate structures, requires careful evaluation to prevent permanent functional and aesthetic sequelae (Døving et al., 2022). Diagnosis is mainly based on cone-beam computed tomography, which allows for the assessment of bone defects, muscle entrapment, and changes in orbital soft tissues, while magnetic resonance imaging is indicated in specific cases, such as optic nerve injury (Døving et al., 2022; Zhou et al., 2021). A complete clinical evaluation, including ocular motility, diplopia, enophthalmos, and signs of the oculocardiac reflex, is essential, especially in "trapdoor" type fractures in children, which constitute a surgical emergency (Heath Jeffery et al., 2022; Døving et al., 2022). Surgical management depends on the extent of the fracture, muscle entrapment, and visual changes. The transconjunctival approach is preferred to minimize scarring and reduce the risk of ectropion, and is indicated for reconstruction of the orbital floor and medial wall (Døving et al., 2022; Persson et al., 2023). Titanium, porous polyethylene, or custom-made (PSI) implants, combined with virtual planning and intraoperative navigation, allow for precise restoration of orbital volume, especially in posterior regions and the orbital apex, reducing diplopia and reinterventions (Persson et al., 2023; Zhou et al., 2021). Complications include persistent diplopia, enophthalmos, and eyelid abnormalities (entropion and ectropion), mainly in cases of multiple surgical exposures or inadequate implant placement (Persson et al., 2023; Døving et al., 2022). Rigorous monitoring of ocular function and standardization of protocols between surgeons and radiologists are essential to optimize outcomes and reduce morbidity (Folkestad et al., 2023; Døving et al., 2022). Thus, the treatment of orbital fractures requires an individualized approach, integration of advanced examinations and precise surgical techniques, with adequate volumetric restoration and technological planning, fundamental to preventing complications and ensuring favorable functional and aesthetic outcomes (Persson et al., 2023; Zhou et al., 2021; Døving et al., 2022).DOI: https://doi.org/10.56238/sevened2026.003-001